Organizational Voice Behaviour and its Investigation in Terms of Organizational Variables - Kok, Sabahat Bayrak; Sarikaya, Mehtap; Coban, Hatice (European Scientific Journal, ESJ, 2016)
Organizational voice described as employeesâ€™ attitude of expressing their opinions to influence organizational activities reluctantly has three varieties of â€œacquiescent voiceâ€ including acquiescence behaviour relying on submission; â€œdefensive voiceâ€ including self-defence behaviour because of a certain fear; and â€œprosocial voiceâ€ behaviour toward others relying on cooperation; and these varieties differentiate according to the motives underneath of organizational voice. In the present study, it was investigated whether organizational voice behaviour and varieties of organizational voice behaviour significant origin of organizational change and development exhibit significant difference according to the demographical variables, or not. To that end, a survey study was conducted on the white-collar employees of the Denizli City companies ranked in the ISO 500 list. In the analysis of data collected from 202 white-collar employees, T-Test and ANOVA methods were employed. As a result of these analyses, it was revealed that organizational voice behaviour varieties displayed by employees were not significantly correlated with any demographical variable statistically.